2005
DOI: 10.1677/jme.1.01833
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of corticotropin-releasing hormone receptor-2 expression in human cord blood-derived cultured mast cells

Abstract: Corticotropin-releasing hormone (CRH) is secreted under stress and regulates the hypothalamic-pituitary-adrenal (HPA) axis; it is also secreted outside the brain where it exerts proinflammatory effects, possibly through mast cell activation. Mast cells are necessary for allergic reactions, but are increasingly implicated in acquired immunity and inflammatory diseases worsened by stress. Acute stress and intradermal CRH induced murine skin mast cell activation and increased vascular permeability that was absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
19
1
Order By: Relevance
“…Venihaki et al (2003) found CRF-R2 mRNA expressed in splenocytes. There is also preliminary evidence for CRF-R2 expression in both the spleen and thymus (Baigent, 2001), as well as on mast cells (Papadopoulou et al, 2005). Thus, our studies do not rule out the possibility that, in other systems or cell types, that CRF-R2 can be immunomodulatory.…”
Section: Discussioncontrasting
confidence: 64%
“…Venihaki et al (2003) found CRF-R2 mRNA expressed in splenocytes. There is also preliminary evidence for CRF-R2 expression in both the spleen and thymus (Baigent, 2001), as well as on mast cells (Papadopoulou et al, 2005). Thus, our studies do not rule out the possibility that, in other systems or cell types, that CRF-R2 can be immunomodulatory.…”
Section: Discussioncontrasting
confidence: 64%
“…The presence of CRHR2 on resident and circulating immune cells such as granulocytes, monocytes, plasma, and mast cells (14,25,26) and its up-regulation on intestinal plasma cells and macrophages in patients with ulcerative colitis (22), along with the altered susceptibility of CRH-deficient mice to inflammatory (27)(28)(29) and autoimmune conditions (30), prompted us to examine intestinal inflammatory responses in CRHR2-null mice. For that purpose, we applied the C. difficile toxin A-mediated mouse model of acute intestinal inflammation, which has been previously used by us to demonstrate a peripheral proinflammatory role for CRH (29,31) mediated, at least in part, by CRHR1 (31).…”
mentioning
confidence: 99%
“…Thus, IL-4 promotes the expression of chymase as well as expression ofFcERI in developing (SCF-dependent) human MCs (32). In addition, IL-4 has been reported to upregulate expression of corticotropin-releasing hormone receptor-2 (CRHR-2) on human mast cells (33). MC stimulation by CRH could lead to secretion of proinflammatory mediators that recruit circulating immune cells to inflammation sites and activate local immune accessory cells as well as peripheral nerves.…”
Section: Origin Ofmast Cells and Regulation Ofgrowthmentioning
confidence: 99%